Post-Communist City on its Way from Grey to Colourful: The Case Study from Slovakia - Alexandra Bitusikova (Fondazione Eni Enrico Mattei (FEEM), 2003)
The paper is a case study of the city of Banska Bystrica in Slovakia in the light of political, socio-economic and cultural changes. It discusses urban diversity and integrity from an anthropological qualitative perspective. On the example of three different historical periods (1918 1948: the democratic Czechoslovakia; 1948 1989: the communist Czechoslovakia; 1989 up to the present: building new democracy in a new state) the study shows transformations of the city and urban life. The research results show how political systems influence conditions, in which urban diversity and heterogeneity develop. The study demonstrates that diversity can grow and flourish only in democracy, which allows differences and pluralism leading to richer and diversified urban life.
Keywords: N30; 330; Urban diversity; post-communist city; democracy; Slovakia